2014
DOI: 10.3390/environments1020137
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Types of Activated Carbon on the Bioaccessibility of 14C-phenanthrene in Sterile and Non-Sterile Soils

Abstract: In this study, the impact of three different types of activated carbon (AC) on the bioaccessibility of 14 C-phenanthrene in non-sterile and sterile soils was investigated. A single dose (1%) of each of the different AC (CB4, CP1 and AQ5000) was blended with soil spiked with 50 mg•kg −1 of 12 C/ 14 C-phenanthrene. The mineralisation of the 14 C-phenanthrene was monitored over a 14 day incubation period by indigenous soil microflora and an enriched inoculum of Pseudomonas sp., while uptake in earthworms, Eisenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 45 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…Analysis of the data suggested that there was a relation between the AC type, and its impact on 14 C-phenanthrene mineralisation in soil. 12,23,26 This indicates that the characteristic of coconut shell based carbon, which has a predominance of pores in the micropore-mesopore range, accounts for 95% of the available internal surface area. Values are mean AE standard error (n ¼ 3) CP1-amended soils, respectively.…”
Section: Effect Of Ac Type On 14 C-phenanthrene Mineralisation In Soilmentioning
confidence: 95%
See 3 more Smart Citations
“…Analysis of the data suggested that there was a relation between the AC type, and its impact on 14 C-phenanthrene mineralisation in soil. 12,23,26 This indicates that the characteristic of coconut shell based carbon, which has a predominance of pores in the micropore-mesopore range, accounts for 95% of the available internal surface area. Values are mean AE standard error (n ¼ 3) CP1-amended soils, respectively.…”
Section: Effect Of Ac Type On 14 C-phenanthrene Mineralisation In Soilmentioning
confidence: 95%
“…2-4; Tables 2-4). 12 An increase in soil-phenanthrene contact time led to a reduction in the rates and extents of 14 C-phenanthrene mineralisation, although it was not signicant in the lower concentrations of AC-amended soils. A comparison CB4, AQ5000 and CP1-amended soils showed that CB4-amended soils generally had the highest extents of 14 Cphenanthrene mineralisation; this was found to be statistically signicant (P < 0.001), when compared to AQ5000-and CP1amended soils (Fig.…”
Section: The Mineralisation Of 14 C-phenanthrene On Acamended Soilmentioning
confidence: 96%
See 2 more Smart Citations
“…This measurement can be valuable in predicting biodegradation endpoints in the assessment of contaminated land (Rhodes et al, 2012;Sanchez et al, 2013;Ortega-Calvo et al, 2015;Ogbonnaya et al, 2016). However, prediction of bioaccessibility has been less successful in larger soil organisms, such as earthworms, high molecular weight (HMW) PAHs contaminated soils and soils with relatively high amounts of black carbon (Hickman and Reid, 2005;Barther and Pelletier, 2007;Papadopoulos et al, 2007;Rhodes et al, 2012;Cui et al, 2013;Oyelami et al, 2014). Thus, identifying a supporting technique that can overcome these barriers with similar efficiency would be valuable for the assessment of contaminated land.…”
Section: Comparative Prediction Of 14 C-phenanthrene Biodegradabilitymentioning
confidence: 99%